Protein Profile of Cod Fish (Euthynnus affinis) Preserved with Pineapple Peel Vinegar (Ananas comosus)-NaCl Formulation Based on Soaking Variations: Profil Protein Ikan Tongkol (Euthynnus affinis) Yang Di Awetkan Dengan Formulasi Cuka Kulit Nanas (Ananas comosus) Dan NaCl Berdasarkan Variasi Perendaman - Mardiyah, Siti; Jannah, Faiqotul; Kartikorini, Nastiti; Supatmi, Supatmi (Medicra (Journal of Medical Laboratory Science/Technology), 2024)
Fish is a food source that is easily damaged. The quality of fish is easily reduced because the water and protein content in fish is quite high so that it rots easily. Therefore, fish require preservation that can maintain the quality of fish, some fishermen usually use formalin as a preservative to preserve fish, but formalin is not allowed in food ingredients because formalin is harmful to health. The use of natural preservatives is an alternative choice for preserving fish. Pineapple skin vinegar is one of the natural preservatives that can be used because it contains acetic acid which functions as an antimicrobial that prevents the growth of bacteria in fish. The purpose of this study was to analyze the description of the protein content of Tuna fish (Euthynnusaffinis) preserved with pineapple skin vinegar (AnanasComosus) and NaCl formulations based on soaking variations. This type of research is descriptive research conducted by grouping fish to determine the protein content of fish incubated for 12 hours in each group. The results showed that 15-minute soaking got an average value of 9.3504%, while 20-minute soaking got an average value of 17.6214%. The conclusion is that the soaking time of pineapple skin vinegar and NaCl got different average values.